Techniques and process of translation as an essential part in written communication in different professional areas - Alas Martínez, Bryan Saúl; Martínez Villacorta, Rosa Saraí; Melara Cañas, Sandra Patricia (Universidad de El Salvador. Facultad de Ciencias y Humanidades., 2024)
Disponible en soporte impreso.